1994
DOI: 10.1523/jneurosci.14-05-02531.1994
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine lesions of the prefrontal cortex in monkeys enhance performance on an analog of the Wisconsin Card Sort Test: possible interactions with subcortical dopamine

Abstract: The effects of 6-hydroxydopamine lesions of the prefrontal cortex in monkeys were investigated on two cognitive tests of prefrontal function, spatial delayed response, and attentional set shifting. The latter test provided a componential analysis of the Wisconsin Card Sort Test, a commonly used clinical test of frontal lobe function in man. Acquisition of a visual compound discrimination requiring a shift of attention from one dimension to another (extradimensional shift), for example, shapes to lines, was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
280
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(313 citation statements)
references
References 55 publications
29
280
4
Order By: Relevance
“…Prefrontocortical serotonin levels were reduced to a much lesser extent, and noradrenergic content was not modified, an important fact because reduced noradrenergic activity after prefrontocortical dopamine loss can lead to paradoxical recovery of extracellular dopaminergic levels (Venator et al, 1999). Interestingly, dopamine and metabolite contents were enhanced in the nucleus accumbens after 6-OHDA lesion, suggesting that there is an inverse relation between mesocortical and mesolimbic dopaminergic systems, as proposed by others Pycock, 1978, 1980;Pycock et al, 1980;Glowinski et al, 1984;Grace, 1991;Roberts et al, 1994;Kolachana et al, 1995;Kurachi et al, 1995). Accumbal DA turnover was reduced after mPFC lesion, a fact that could be interpreted as reflecting a decrease in firing of DA neurons projecting to nucleus accumbens after DA lesion of the mPFC, in accordance with electrophysiological studies (Harden et al, 1998).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Prefrontocortical serotonin levels were reduced to a much lesser extent, and noradrenergic content was not modified, an important fact because reduced noradrenergic activity after prefrontocortical dopamine loss can lead to paradoxical recovery of extracellular dopaminergic levels (Venator et al, 1999). Interestingly, dopamine and metabolite contents were enhanced in the nucleus accumbens after 6-OHDA lesion, suggesting that there is an inverse relation between mesocortical and mesolimbic dopaminergic systems, as proposed by others Pycock, 1978, 1980;Pycock et al, 1980;Glowinski et al, 1984;Grace, 1991;Roberts et al, 1994;Kolachana et al, 1995;Kurachi et al, 1995). Accumbal DA turnover was reduced after mPFC lesion, a fact that could be interpreted as reflecting a decrease in firing of DA neurons projecting to nucleus accumbens after DA lesion of the mPFC, in accordance with electrophysiological studies (Harden et al, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…The mPFC also plays an important role in the dopaminergic system network, since it receives input from the mesocortical dopamine (DA) system, and sends efferents to the nucleus accumbens, dorsal striatum, and midbrain DA cell groups Pycock, 1978, 1980;Pycock et al, 1980;Glowinski et al, 1984;Grace, 1991;Roberts et al, 1994;Kolachana et al, 1995;Kurachi et al, 1995). Dopaminergic activity in the mPFC is quite important in the neuromodulation of the 'cognitive functions' of the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Because a delay period is interposed between trials, the rat is required to briefly maintain information regarding the next choice "on-line," thus, requiring the working memory construct. This task is closely linked with the function of the frontal cortex and its dopaminergic innervation (Brozoski et al 1979;Kolb 1984;Goldman-Rakic 1987; Bubser and Schmidt 1990;Roberts et al 1994). Longterm PCP administration produces delay-dependent performance impairments on a variable-delay spatial T-maze alternation task (Jentsch et al 1997b).…”
Section: Effects Of Long-term Pcp Administration On Cognitive Behaviormentioning
confidence: 99%
“…It could be hypothesized that reduced cortical dopamine transmission induced by long-term PCP exposure may be associated with a hyperactivity of subcortical dopamine systems (as with acute administration), because the mesocortical and mesolimbic dopamine systems demonstrate an inverse relationship in animals; that is, hypoactivity of the cortical dopamine system propagates subcortical dopamine hyperactivity (Pycock et al 1980;Grace 1991;Deutch 1992;Roberts et al 1994). Although no changes in basal, resting dopamine utilization in the nucleus accumbens were noted after subchronic treatment with PCP (Jentsch et al 1997b,c), we have now found that the mesolimbic dopamine pathway has increased responsivity to haloperidol, d-amphetamine, or mild stress (Jentsch et al 1998c).…”
Section: Subcortical Dopamine Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation